Nuclear Receptor Liver X Receptor Is O-GlcNAc-modified in Response to Glucose - Anthonisen, Elin Holter (American Society for Biochemistry and Molecular Biology, 2010)
Post-translational modification of nucleocytoplasmic proteins by O-linked β-N-acetylglucosamine (O-GlcNAc) has for the last 25 years emerged as an essential glucose-sensing mechanism. The liver X receptors (LXRs) function as nutritional sensors for cholesterol-regulating lipid metabolism, glucose homeostasis, and inflammation. LXRs are shown to be post-translationally modified by phosphorylation, acetylation, and sumoylation, affecting their target gene specificity, stability, and transactivating and transrepressional activity, respectively. In the present study, we show for the first time that LXRα and LXRβ are targets for glucose-hexosamine-derived O-GlcNAc modification in human Huh7 cells. Furthermore, we observed increased hepatic LXRα O-GlcNAcylation in vivo in refed mice and in streptozotocin-induced refed diabetic mice. Importantly, induction of LXRα O-GlcNAcylation in both mouse models was concomitant with increased expression of the lipogenic gene SREBP-1c (sterol regulatory element-binding protein 1c). Furthermore, glucose increased LXR/retinoic acid receptor-dependent activation of luciferase reporter activity driven by the mouse SREBP-1c promoter via the hexosamine biosynthetic pathway in Huh7 cells. Altogether, our results suggest that O-GlcNAcylation of LXR is a novel mechanism by which LXR acts as a glucose sensor affecting LXR-dependent gene expression, substantiating the crucial role of LXR as a nutritional sensor in lipid and glucose metabolism.